2016
DOI: 10.1128/aac.02334-15
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the Optimal Predictor of Ciprofloxacin Resistance in Klebsiella pneumoniae by Using In Vitro Dynamic Models

Abstract: There is growing evidence of applicability of the hypothesis of the mutant selection window (MSW), i.e., the range between the MIC and the mutant prevention concentration (MPC), within which the enrichment of resistant mutants is most probable. However, it is not clear if MPC-based pharmacokinetic variables are preferable to the respective MIC-based variables as interstrain predictors of resistance. To examine the predictive power of the ratios of the area under the curve (AUC 24 ) to the MPC and to the MIC, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Since the MSW hypothesis predicts the enrichment of resistant mutants at antibiotic concentrations above the MIC, but below the mutant prevention concentration (MPC) the concentration-resistance relationship can be described by an extremum-containing function. This also has been confirmed in further in vitro studies with fluoroquinolones [6,[8][9][10][11][12][13][14][15][16], glycopeptides and lipopeptides [17], and oxazolidinones [18] that demonstrate bell-shaped relationships between the amplification of resistant mutants or loss in susceptibility of antibiotic-exposed bacteria and AUC 24 or AUC 24 /MIC. It was this ratio that allows prediction of strain-independent resistance thresholds, i.e., the "antimutant" AUC 24 /MIC ratios, which were surprisingly less variable than the respective AUC 24 /MPC ratios among fluoroquinolone-exposed Gram-negative bacteria [12,15,16] but not such exposed Gram-positive bacteria [19].…”
Section: Introductionsupporting
confidence: 55%
“…Since the MSW hypothesis predicts the enrichment of resistant mutants at antibiotic concentrations above the MIC, but below the mutant prevention concentration (MPC) the concentration-resistance relationship can be described by an extremum-containing function. This also has been confirmed in further in vitro studies with fluoroquinolones [6,[8][9][10][11][12][13][14][15][16], glycopeptides and lipopeptides [17], and oxazolidinones [18] that demonstrate bell-shaped relationships between the amplification of resistant mutants or loss in susceptibility of antibiotic-exposed bacteria and AUC 24 or AUC 24 /MIC. It was this ratio that allows prediction of strain-independent resistance thresholds, i.e., the "antimutant" AUC 24 /MIC ratios, which were surprisingly less variable than the respective AUC 24 /MPC ratios among fluoroquinolone-exposed Gram-negative bacteria [12,15,16] but not such exposed Gram-positive bacteria [19].…”
Section: Introductionsupporting
confidence: 55%
“…The Figs show that accurate bell-shaped relationships fitted with Gaussian function were observed. Similar bell-shaped "PK/PD index-resistance" relationships were previously reported in several studies with non-beta-lactam antibiotics with an account of the mutant selection window (MSW) hypothesis [10][11][12][13][14][15][16][17]; in this regard, beta-lactam antibiotics were not well described. Interestingly, despite meropenem degradation throughout time-kill experiments and the resultant pharmacokinetic profiles that differed significantly from targets, T MSW values, calculated with desired meropenem concentrations, were consistent with the enrichment of the bacterial population with resistant cells.…”
Section: Plos Onesupporting
confidence: 74%
“…To address these issues we tested the well-known mutant selection window hypothesis with meropenem. The mutant selection window (MSW) hypothesis is applicable [10] to explain resistance patterns of several classes of antibiotics [11][12][13][14][15][16][17]; however, only a few such studies have been reported with beta-lactams [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…The MSW comprises a specific drug concentration range in which mutant strains with reduced susceptibility can be selected ( Drlica and Zhao, 2007 ; Blondeau, 2009 ). It has been confirmed in many antibiotics such as fluoroquinolones ( Strukova et al, 2016 ), oxazolidinones ( Alieva et al, 2018 ), aminoglycosides ( Ni et al, 2016 ). MPC is defined as the lowest concentration that blocks the emergence of first-step resistant mutants in a large susceptible population, usually more than 10 10 colony forming unit (CFU)/mL bacteria ( Drlica, 2003 ).…”
Section: Introductionmentioning
confidence: 97%